Development of a KDP crystal growth system based on TRM and characterization of the grown crystals - Javidi, S.; Faripour, H.; Esmaeil Nia, M.; Sepehri, K.F.; Ali Akbari, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
A solution growth system has been built based on temperature reduction
method [1]. A few KDP crystals were grown by the system up to 160×40×38 mm
dimensions. Spectrophotometer transmission spectra from (100) planes of the grown
crystals show about 86 % transmission in the visible region. XRD analysis, laser damage
threshold, and microhardness of the crystals were determined. The etching behavior of
surface features of grown KDP single crystals was studied in different etchants.